Comparison of anatomical landmarks and dimensions in a hypospadiac glans with those of a normal glans - Anjan Kumar Dhua; Sachit Anand; Sandeep Agarwala; Veereshwar Bhatnagar (Wolters Kluwer Medknow Publications, 2018)
Aim of the Study: The aim of this study is to establish ventral glans length (VGL), meatus (M) size, and their ratio VGL/M (R) in normal Indian boys and to compare these with the respective equivalent dimensions in boys with distal and mid-penile hypospadias using anatomic landmarks. Methods: Normal boys were designated as Group A (n = 108), and the boys with hypospadias were designated as Group B (n = 81). The anatomical landmarks marked on the glans were measured using a digital camera and appropriate software. Results: The mean age of the boys in Groups A and B was 4.26 ± 3.59 (range 0.5-12) and 3.82 ± 2.85 (0.7-11) years, respectively. The observed mean values in Group A for VGL-A, M-A, and R-A were 3.05 ± 1.27 (range 1.19-8.09), 4.3 ± 1.23 (range 1.61-7.04), and 0.8 ± 0.45 (range 0.27-2.1) mm, respectively. The observed mean values in Group B for VGL-B, M-B, and R-B were 3.77 ± 0.81 (range 12.41-5.2), 3.27 ± 0.71 (range 2.25-5.34), and 1.17 ± 0.26 (range 0.84-1.86) mm, respectively. Comparison of R-A and R-B showed a statistically significant difference (P < 0.0001). Conclusions: The dimensions and the studied ratio between a hypospadiac glans and a normal glans differed significantly. The ratio between VGL and M was 0.8 in normal boys. In comparison, the ratio between the equivalent VGL and M in the hypospadiac boys was 1.17. During glansplasty in surgery for hypospadias, this factor should be taken into consideration to avoid the creation of long and tight ventral glans closure.